Eksistensi Ilmu Komunikasi dalam Kehidupan Manusia - Effendy, Erwan; Ginting, Alya Rahmadhani Br; Rafi’ie, M. Hafizh; Purba, M. Naufal Dzakwan; Anggraini, Rahadian Tri (Lembaga Yasin AlSys, 2023)
This research seeks to explore the role of communication science in the human experience. It employs a qualitative research approach, which involves presenting data through a series of sentences. The methodology employed in this study is descriptive in nature. The findings of this investigation highlight communication science as a discipline that delves into the principles, theories, and concepts surrounding the human communication process. More precisely, this field investigates the transmission, reception, and comprehension of information by individuals, groups, organizations, and society in various contexts. Communication science serves not only as an academic domain but also as a valuable practical skill deeply integrated into people's daily lives. Its presence assists individuals in comprehending, enhancing, and deepening their interactions with the world. Communication science holds significant importance in human existence because communication is the primary means by which humans connect, exchanging ideas, experiences, and emotions. The subsequent points emphasize why the significance of communication science in human life cannot be overstated: It aids in fostering and sustaining healthy interpersonal relationships and helps individuals comprehend the influence of mass media on thought patterns, behavior, and perceptions.